A multicentric study on dermoscopic patterns and clinical–dermoscopic–histological correlates of basal cell carcinoma in Indian skin. (1st November 2022) - Vinay, Keshavamurthy; Ankad, Balachandra S.; Narayan R., Vignesh; Chatterjee, Debajyoti; Bhat, Yasmeen Jabeen; Neema, Shekhar; Shah, Swapnil; Chauhan, Payal; Khare, Soumil; Rajput, Chetan; Jadhav, Prashant; Beergouder, Savitha L.; et al.
Abstract: Background: Literature on the dermoscopic patterns of basal cell carcinoma (BCC) in India is limited. Aim: To describe the dermoscopic pattern and dermoscopic–histopathological correlation in a large cohort of patients with BCC from India, with a particular focus on skin of colour (SOC). Methods: This retrospective study was conducted under the aegis of the Dermatoscopy Society of India. Clinical details were collected, and two lead authors independently analysed dermoscopic images of BCC for a predefined set of characteristics. Histopathological slides/blocks were reviewed, and dermoscopic–histological correlation attempted. Results: In total, 143 patients with BCC and skin phototypes IV–VI were included. The mean largest BCC diameter was 3.10 ± 3.68 cm and there was a significant but weak association between duration and largest dimension of the lesion (Spearman ρ = 0.33, P < 0.01). Nearly half of the cases were diagnosed with pigmented BCC and the most common histological subtype was nodular BCC (37.9%). Dermoscopically, blue–grey dots and arborizing vessels were the most common features (60.0%). Pigmentary changes were found in the majority of cases, and included blue–white veil, blue–grey ovoid nests and maple leaf‐like areas. A third of our patients had short linear telangiectasia, polymorphic vessels and regular dotted vessels, and another third exhibited a dermoscopic rainbow effect. Arborizing vessels were significantly more common with micronodular (78.9%) and nodular variants (74.1%, P = 0.05), whereas regular dotted vessels (68.4%, P = 0.04), blue–white veil (84.2%, P = 0.02) were significantly associated with micronodular variant. Conclusion: The dermoscopic patterns of blue–white veil and regular dotted vessels are indicators towards micronodular BCC in SOC and can help in prioritizing treatment. Abstract : We assessed the dermoscopic features of basal cell carcinoma (BCC) in patients with skin of colour (SOC) in India, and determined their association with histological subtype. This should be helpful in prioritizing high‐risk BCC for treatment in patients with SOC.